PENGARUH PROFESIONALISME, ETIKA PROFESI, PENGALAMAN AUDITOR DAN INDEPENDENSI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empris BPKP RI Perwakilan Provinsi Riau) - Lia Edli Syaravina; Hardi Hardi; Yessi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research has been done by method of survey to BPKP deligation of Riau’s province. This research has purpose to find out the empiric evidence influence to professionalism, ethic of profession, experience of auditor and independence toward to the consideration of materiality. The population of this research are auditors who work in BPKP delegation of Riau’s province. The number of sample are taken same with the number of respondent that are 104 peoples. Types of data that used is primer data with collecting data method uses quesioner. Analysis data method is multiple regression with the assistance of software SPSS version 17.00. The result of research shows that professionalism, ethic of profession, experience of auditor and independence are influential toward to the consideration of materiality with significant value of professionalism is 0.026, Ethic of profession is 0.046, experience of auditr is 0.043 and independence is 0.031. vlue o alph is 0.05. value of adjusted R square is 0.675. It means as 67,5% of independents variable in this research are able to influence the variable of dependent, the rest mount is 32,5% are influenced of the other varablee that are not registered into this model of regression.Keywords:Professionalism, Ethic of profession, Experience of auditor, Independence and the consideration of materiality